Pengaruh Lingkungan kerja,Kepemimpinan dan Motivasi Terhadap Semangat Kerja Guru - Dedeh Imam Fatmasari (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2021)
This study aims to determine the effect of work environment, leadership, motivationon teacher morale. After testing, it is concluded that work environment, leadership, motivation,have a significant effect on teacher morale. Simultaneously it is known that there is a significantinfluence between work environment, leadership, motivation and collectively towards the moraleof the teacher.Based on the statistical test, an adjusted R square (R2) of 0.660 or 66.0% was obtained, whichindicates that 66.0% of changes in teacher morale variables can be explained by variables ofwork environment, leadership, motivation, while the remaining 31.2% is explained by othervariables outside the model. The result of 0.660 shows that the relationship between theseindependent variables together on the teacher work spirit variable has a strong andunidirectional relationship. Meanwhile, each of the independent variables affecting teachermorale are:Y = 0.776 + 0.611 X2 + 0.125 X3 + 0.461 X4 means a constant. Based on the t test, it was foundthat the variables of competence and enthusiasm had no effect on teacher morale, and othervariables had an effect. For the F test, the results show that together the independent variableshave an effect on the morale of teachers in SMK RADEN PATAH Mojosari.